2011
DOI: 10.1161/atvbaha.110.215756
|View full text |Cite
|
Sign up to set email alerts
|

Worsening of Diet-Induced Atherosclerosis in a New Model of Transgenic Rabbit Expressing the Human Plasma Phospholipid Transfer Protein

Abstract: Objective-Plasma phospholipid transfer protein (PLTP) is involved in intravascular lipoprotein metabolism. PLTP is known to act through 2 main mechanisms: by remodeling high-density lipoproteins (HDL) and by increasing apolipoprotein (apo) B-containing lipoproteins. The aim of this study was to generate a new model of human PLTP transgenic (HuPLTPTg) rabbit and to determine whether PLTP expression modulates atherosclerosis in this species that, unlike humans and mice, displays naturally very low PLTP activity.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
39
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(40 citation statements)
references
References 46 publications
1
39
0
Order By: Relevance
“…13 In rabbits, overexpression of PLTP-increased atherosclerotic lesions after a high-fat diet feeding when compared with controls. 14 In general, PLTP is a risk factor of atherosclerosis in animal models. However, whether PLTP can affect the stability of atherosclerotic plaque and the mechanism involved are still unknown.…”
mentioning
confidence: 99%
“…13 In rabbits, overexpression of PLTP-increased atherosclerotic lesions after a high-fat diet feeding when compared with controls. 14 In general, PLTP is a risk factor of atherosclerosis in animal models. However, whether PLTP can affect the stability of atherosclerotic plaque and the mechanism involved are still unknown.…”
mentioning
confidence: 99%
“…Overexpression of apoE decreased levels of apoB-containing lipoproteins in mice (Shimano, 1992) but increased cholesterol levels in plasma and LDL in rabbits (Fan, 1998). In addition, overexpression of PLTP increased HDL-cholesterol and apoA-I levels but did not affect LDL-cholesterol in mice (Jiang, 1996), while it increased LDL-cholesterol and did not affect HDL in rabbits (Masson, 2011). These differences may be due to high CETP activity in rabbits and no CETP activity in mice.…”
Section: Hdl Receptorsmentioning
confidence: 90%
“…In PLTP transgenic mice, PLTP did not affect lipid levels of apoB-containing lipoproteins but increased phospholipid and cholesterol levels in HDL (Jiang, 1996). However, overexpression of PLTP in rabbits increased cholesterol levels in apoB-containing lipoproteins but had no effect on HDL lipids in a high-cholesterol deiet feeding (Masson, 2011). These differences in the function of PLTP between mice and rabbits may be due to fundamental differences in lipoprotein metabolism, such as CETP activity in the plasma and apobec-1 expression in the liver.…”
Section: Transfer Of Lipids From Hdl To Apob-containing Lipoproteinsmentioning
confidence: 91%
See 1 more Smart Citation
“…The role of PL-TP in HDL remodeling is influenced by particle protein composition and triglycerides concentration [11]. Some experimental trials have demonstrated the PLTP pro-atherogenic role [12] [13], and in humans PLTP is associated with cardiovascular complications [14]. HDL exerts multiple atheroprotective functions, among them antioxidant activity, mainly performed by paraoxonase (PON-1), by hydrolysis of phospholipids and cholesterol ester hydroperoxides [15].…”
Section: Introductionmentioning
confidence: 99%